Urticaria: Collegium Internationale Allergologicum (CIA) update 2020 - Maurer, Marcus; Eyerich, Kilian; Eyerich, Stefanie; Ferrer, Marta; Gutermuth, Jan; Hartmann, Karin; Jakob, Thilo; Kapp, Alexander; Kolkhir, Pavel; Larenas-Linnemann, Désirée; Park, Hae-Sim; Pejler, Gunnar; et al. (International archives of allergy and immunology, 2020)
This update on chronic urticaria (CU) focuses on the prevalence and pathogenesis of chronic spontaneous urticaria (CSU), the expanding spectrum of patient-reported outcome measures (PROMs) for assessing CU disease activity, impact, and control, as well as future treatment options for CU. This update is needed, as several recently reported findings have led to significant advances in these areas. Some of these key discoveries were first presented at past meetings of the Collegium Internationale Allergologicum (CIA). New evidence shows that the prevalence of CSU is geographically heterogeneous, high in all age groups, and increasing. Several recent reports have helped to better characterize two endotypes of CSU: type I autoimmune (or autoallergic) CSU, driven by IgE to autoallergens, and type IIb autoimmune CSU, which is due to mast cell (MC)-targeted autoantibodies. The aim of treatment in CU is complete disease control with absence of signs and symptoms as well as normalization of quality of life (QoL). This is best monitored by the use of an expanding set of PROMs, to which the Angioedema Control Test, the Cholinergic Urticaria Quality of Life Questionnaire, and the Cholinergic Urticaria Activity Score have recently been added. Current treatment approaches for CU under development include drugs that inhibit the effects of signals that drive MC activation and accumulation, drugs that inhibit intracellular pathways of MC activation and degranulation, and drugs that silence MCs by binding to inhibitory receptors. The understanding, knowledge, and management of CU are rapidly increasing. The aim of this review is to provide physicians who treat CU patients with an update on where we stand and where we will go. Many questions and unmet needs remain to be addressed, such as the development of routine diagnostic tests for type I and type IIb autoimmune CSU, the global dissemination and consistent use of PROMs to assess disease activity, impact, and control, and the development of more effective and well-tolerated long-term treatments for all forms of CU.
Gesehen am 29.04.2021